Epidemiological Study of Asthma Prevalence and Management among Primary School Students in Al-Hilla City, Iraq - Alsaadi , Ismael Mohammed; Shlash, Ahmed Mohammed Jasim; AL- Maamouri, Noor Fadhil; Salman, Fatima Kamil (Journal of Biomedicine and Biochemistry, 2025)
Background: Asthma is a prevalent chronic respiratory disease that significantly impacts children’s health, school attendance, and academic performance. This study investigates the prevalence, risk factors, and management of asthma among primary school students in Al-Hilla City, Iraq. Methods: A cross-sectional study was carried out on 300 students from five non randomly selected primary schools in Al-Hilla city, during the academic year 2024-2025. The questionnaire was developed by the researcher. Data were analyzed by SPSS, version 25, software. A P-value of ≤ 0.05 was considered statistically significant. Results: The findings revealed an overall asthma prevalence of 12%, with higher rates in urban areas (15%) compared to suburban areas (9%). Key risk factors included environmental pollution (55%), dust storms (47%), indoor pollutants (37%), a family history of asthma (40%), and low socioeconomic status (50%). Asthma significantly affected students’ health, leading to frequent absenteeism (65%), reduced physical activity (58%), and lower academic performance (45%). Asthma management practices in schools were found to be inadequate, with inconsistent medication use (40%) and limited access to peak flow meters (15%). Conclusion & Recommendation: The study concluded that asthma is a common health problem among students, affecting 12% of the participants, with a significantly higher incidence in urban areas compared to suburban areas. Environmental, social, and economic factors—particularly pollution, dust storms, indoor pollutants, family history, and low income—play a significant role in increasing the risk of asthma. The study highlights the need for improved asthma management protocols in schools, better environmental policies to reduce pollution, and enhanced education for both students and school staff on asthma care.